Application of Fish Embryo Assay Using Zebrafish and Oryzias latipes for Toxicity Testing and Deriving Water Quality Criteria - Lia Kim; Youn-Joo An (Applied Sciences)
To protect aquatic organisms in ecosystems, each country and continental union has established guidelines for deriving the water quality standards (WQS) of specific substances. These guidelines mandate the use of acute and chronic toxicity data for fish, which are high-trophic-level organisms. However, due to increasing concerns about animal welfare and experimental ethics, there is a growing need for alternative methods to determine substance toxicity in fish. Fish toxicity tests using early life stages, such as embryos or larvae, have been utilized as alternative methods for adult fish toxicity assays. This review of the WQS guidelines and relevant test protocols confirmed the classification of acute and chronic toxicity in fish assays using different developmental stages. Fish toxicity data derived from exposure periods longer than one week using embryonic- or larval-stage organisms can be considered as indicative of chronic toxicity. There is a high correlation between fish embryo toxicity and adult effects, suggesting that fish embryo toxicity tests with appropriate exposure durations could replace adult fish toxicity tests, addressing experimental animal ethics concerns.